Mitigating transport stress in sheep: impacts of intramuscular quercetin and grape seed extract on metabolic, oxidative, and meat quality parameters - Mutlu, Muhsin; Tatli Seven, Pinar; Seven, Ismail; Aslan, Abdullah; Sila Cicek, Miray; Iflazoglu Mutlu, Seda (Wiley, 2026)
Background: Transportation is a major stressor in livestock production, adversely affecting animal welfare, physiological status, and meat quality. Oxidative stress and metabolic imbalances induced by transport conditions can lead to significant economic losses. The use of natural antioxidants has been proposed as a strategy to mitigate these negative effects. This study aimed to evaluate the effects associated with intramuscularly administered quercetin (QUE) and grape seed extract (GSE) prior to transport during the winter season on body weight, serum biochemical responses, oxidative stress markers, and meat quality parameters, including carcass pH and fatty acid profile in sheep subjected to road transport. Results: Twenty-four 12-month-old Akkaraman sheep were randomly allocated to four groups (n = 6): control, GSE50 (50 mg kg(-1) grape seed extract), GSE100 (100 mg kg(-1) grape seed extract), and QUE100 (100 mg kg(-1) quercetin). Malondialdehyde (MDA) levels differed among groups, with lower values observed in antioxidant-treated animals; however, baseline variability may have contributed to post-transport differences. Transport led to significant body weight loss in all groups (P < 0.001), with the least reduction observed in the QUE100 group (P = 0.105 among groups). In contrast, carcass pH values showed minimal variation among groups, with differences not exceeding 0.22 units (P = 0.155), and fatty acid composition of longissimus thoracis (LT) muscle (P > 0.05 for all fatty acids) did not differ significantly among groups. Conclusion: These findings suggest that natural bioactive compounds may be associated with improved physiological responses under transport-related stress conditions. (c) 2026 Society of Chemical Industry.
Keywords: grape seed extract; meat quality; oxidative stress; quercetin; sheep; transport stress